Challenges to Prevent Unhealthy Eating Behaviors of Adults - Natalia Elisa Rakinaung; Helly Budiawan; Martinus Lazar (GLOBAL HEALTH SCIENCE GROUP, 2022)
Preventing non-communicable diseases has always been enormous challenge for health workers, and unhealthy eating behavior is one of the causes of several non-communicable diseases such as hypertension, diabetes mellitus, and heart diseases. Nowadays are still many adults who adapt unhealthy eating behavior and this can also affect the family and everyone in the environment. The challenges of health workers in educating adults to have healthy eating behaviors are related to their habits, culture and awareness which are influenced by gender, marital status, knowledge about healthy food, family income, and ethnicity of adults. The aim of this study is to identify the factors related to unhealthy eating behaviors of adults in Tomohon City, North Sulawesi, Indonesia. This cross-sectional study was conducted to Adults in Woloan Village, Tomohon City. The Respondent in this study were 36 adults aged between 23 and 50 years, was taken with purposive sampling technique, completed questionnaire on sociodemographic factors (age, gender, marital status, and family income), knowledge of healthy food, and eating behavior. The data analysis using descriptive analysis and chi-square test. The study revealed that ethnic groups not related with eating behavior. However, knowledge of healthy food and family income were significant related to unhealthy eating behavior of adults. Knowledge of healthy food and family of adults are significant factors that can trigger unhealthy eating behavior of adults, and these also are considered as challenges for health workers to provide suitable health interventions in preventing unhealthy eating behavior of adults.